Autism and toe-walking: Are they related? Trends and treatment patterns between 2005 and 2016. (August 2019) - Leyden, J.; Fung, L.; Frick, S.
Abstract: Purpose: This study quantified toe-walking trends and treatment decisions in patients with autism spectrum disorder (ASD) in the United States between 2005 and 2016 using a large national private-payer database. Methods: A retrospective database review was performed on paediatric patients with ASD, and for International Classification of Diseases-9/10 diagnosis codes for toe-walking. Patients were filtered based on treatment type by Current Procedural Terminology (CPT) code. Continued toe-walking rates were assessed for each patient population and treatment group. A Pearson's chi-squared test was used to evaluate differences in group characteristics. Results: Of 2 221 009 paediatric patients in the database, 5739 patients had a diagnosis of ASD, and 8.4% of patients with ASD also had a diagnosis of toe-walking (n = 484). For typically developing children in the database, 0.47% of patients had a diagnosis of persistent toe-walking. In all, 59.3% of ASD patients underwent physical therapy, 7.4% serial casting and 3.3% surgical correction, compared with 38.1%, 3.6% and 1.2% of normally developing children, respectively (chi-square 6.4031; p < 0.040699). Without intervention, 63.6% of patients with ASD continued to toe-walk within ten years of their diagnosis, with 19.3% of patients without ASD (chi-square 82.9762; p < 0.0001). Conclusion: This study supports the association between a greater prevalence of toe-walking in children with ASD. We showed that patients with ASD and toe-walking receive surgical correction at nearly triple the rate of children without ASD who toe-walk. The continued rate of toe-walking is comparable between treatment groups as well as between ASD and typically developing children. Typically developing children have higher rates of toe-walking resolution without intervention than children with ASD. Level of evidence: Level II